Bridging Academic Excellence and Licensure Success: Unveiling the Pathway for Future Educators - Rubio, Allyn Mae; Matalines, Ana Marie; Malinao, Rodceal; Condes, Rikka Bianca (Journal of Interdisciplinary Perspectives, 2025)
This study investigated the correlation between the academic performance of teacher education graduates and their outcomes in the Licensure Examination for Teachers (LET) at Davao del Sur State College. Despite the critical role of licensure exams in ensuring teacher quality, the existing literature has yielded inconsistent findings regarding the predictive power of academic performance for LET results. The primary objective of this research was to determine the relationship between undergraduate performance in General Education, Professional Education, and Specialization, and LET ratings. Employing a descriptive correlational research design, data were collected from graduates, with their academic performance measured by General Point Average (GPA) and LET ratings sourced from the Professional Regulation Commission. The analysis revealed a strong positive correlation between undergraduate performance in Professional Education and General Education and LET results, whereas a weak correlation was observed in Specialization. These findings suggest that enhancing curricula in General and Professional Education could significantly improve LET outcomes. The study underscores the need for a comprehensive review framework to align educational practices with licensure competencies, ultimately fostering a higher-quality education for future teachers.